2010
DOI: 10.1186/1471-2229-10-121
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and diversity along an altitudinal gradient in Ethiopian barley (Hordeum vulgare L.) landraces revealed by molecular analysis

Abstract: BackgroundAmong the cereal crops, barley is the species with the greatest adaptability to a wide range of environments. To determine the level and structure of genetic diversity in barley (Hordeum vulgare L.) landraces from the central highlands of Ethiopia, we have examined the molecular variation at seven nuclear microsatellite loci.ResultsA total of 106 landrace populations were sampled in the two growing seasons (Meher and Belg; the long and short rainy seasons, respectively), across three districts (Ankob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 67 publications
7
25
1
Order By: Relevance
“…This is in agreement with what has been observed in different species where such comparisons have been made directly [5] or indirectly [8], [23]. This is further confirmation that in-situ conservation of landrace populations is an effective and valuable strategy to preserve crop genetic resources [7].…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with what has been observed in different species where such comparisons have been made directly [5] or indirectly [8], [23]. This is further confirmation that in-situ conservation of landrace populations is an effective and valuable strategy to preserve crop genetic resources [7].…”
Section: Discussionsupporting
confidence: 91%
“…Nielsen et al (2014), Das et al (2013), and Montilla-Bascón et al (2013) indeed reported lower gene diversity in wheat (0.384), rice (0.547) and oat (0.29), respectively. Conversely, R ST may reveal better differentiation, as it is independent of the stepwise mutation process (Hadado et al, 2010). In our study, the private alleles to the five northern populations (Beja, Kef, Siliana, Zaghouan, and Bizerte) represent 56% of the total private alleles assessed in the 11 populations.…”
Section: Genetic Polymorphismmentioning
confidence: 56%
“…The total number of effective alleles was 92.25. Comparable levels of low heterozygosity were reported when microsatellites were applied for Ethiopian (Hadado et al, 2010;Samberg et al, 2013) and Moroccan (Jensen et al, 2013) barley landraces. A total of 227 genotypes were scored with an average of 10.81 genotypes per locus (Table 3).…”
Section: Genetic Polymorphismmentioning
confidence: 91%
See 1 more Smart Citation
“…In plants with a wide distribution, phenological traits and adaptive molecular variance can be expected to vary clinally along climatic gradients [43], [44]. As examples, latitudinal clines in flowering time have been predicted and shown in accessions of the annual Arabidopsis thaliana [43].…”
Section: Discussionmentioning
confidence: 99%